Molecular characterization of genetic diversity within the Africa/Middle East/Asia Minor and Sub-Saharan African groups of the Bemisia tabaci species complex - (:unkn) unknown (My University, 2013)
Bemisia tabaci Gennadius is a major plant pest in many agricultural systems worldwide. It is a complex of cryptic species that differ in many ecological respects, including damage-causing potential. Monitoring the genetic composition of B. tabaci populations in the field is, therefore, essential for achieving effective control. Sequencing is costly and time consuming; thus, efficient diagnostic tools must be developed to perform epidemiological studies involving hundreds of individuals. Here, we describe a polymerase chain reaction (PCR) restriction fragment length polymorphism (RFLP) method for identifying all the putative species comprising the Africa/Middle East/Asia Minor group, including those that are the most devastating crop pests. Moreover, intra-specific diversity associated with specific symbiotic bacteria known to manipulate insect host phenotypes can also be detected. In addition, this method discriminates between the Africa/Middle East/Asia Minor and the Sub-Saharan African groups, which are sympatric in some areas. This simple, reliable and cost-effective diagnostic tool is ideal for the rapid analysis of a high number of individuals and, thus, has potential applications in field contexts, where it could provide valuable baseline information for pest management programs.
Keywords: African Research